Capital Structure Choices and Stock Market Volatility: Evidence from Chinese Listed Firms. Issue 1 (2nd January 2023) - Vuong, Thi Huong Giang; Wu, Yang-Che; Weng, Tzu-Ching; Nguyen, Huu Manh; Vo, Xuan Vinh
Abstract: An essential issue of listed firms is adjusting their capital structure as stock market volatility increases. Our study examines this concern by using panel data of the Shanghai Stock Exchange for the period 2008–2018. We find that stock market volatility has immediate positive effects on both total market leverage and short-term market leverage but a negative influence on the long-term market leverage of Chinese listed firms. In this scenario, Chinese listed firms adjust their debt structure by using high bank debts and cutting trade credit due to lower debt costs. Further analyses confirm that the proportion of bank debts to total debts visibly increases while that of trade credit to total debts distinctly decreases. Furthermore, we implement robust tests regarding potential issues, such as sample selection, model selection, endogenous factors, and quantile regression to strengthen the robustness of the main findings. This study provides the first framework for investigating a link between the stock market volatility and capital structure decisions in a typical emerging market.